Inflammation, impaired motor function and visceral hypersensitivity: the main mechanisms of functional disorders of the gastrointestinal tract (materials of the Expert Council and literature review) - V. T. Ivashkin; I. V. Maev; A. S. Trukhmanov; A. A. Sheptulin; T. L. Lapina; V. I. Simanenkov; K. A. Sokolov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To review the main mechanisms of functional disorders of the gastrointestinal tract and to present the materials of an Expert Council, which was held on 10 December 2021 in Moscow.Key points. The pathogenesis of the most common functional diseases of the gastrointestinal tract — functional dyspepsia (FD) and irritable bowel syndrome (IBS) is multifactorial and includes motor disorders of various parts of the gastrointestinal tract, visceral hypersensitivity, changes in the intestinal microbiome, impairment of the permeability of the protective barrier, low-grade inflammation of the gastrointestinal mucosa, etc. This often leads to the prescription of a complex of various medications to such patients, which increases the risk of undesirable drug interactions and side effects. Multitargeted therapy involves the use of drugs that simultaneously affect different pathogenetic links. One of these drugs is Iberogast®, which normalizes gastrointestinal motility and visceral sensitivity, has an anti-inflammatory action and is highly effective in treatment of FD and IBS.Conclusion. In the treatment of functional gastrointestinal diseases characterized by multifactorial pathogenesis, preference should be given to multi-targeted therapy with the use of drugs that have an effect on its various links.